Pengaruh Budaya Organisasi, Motivasi Kerja dan Disiplin Kerja Terhadap Kinerja Guru MA AL-WASHLIYAH Kota Tebing Tinggi - Muhammad Reyza; Muhammad Farhan Daffazha Rangkuti; Suci Etri Jayanti. S; Cia Cai Cen (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study was conducted with the aim of evaluating the influence of organizational culture, work motivation and work discipline on the performance of teachers at Ma Al-Washliyah Tebingtinggi City. The number of respondents in this study was 34 people. In this study, the sampling technique used was Total Sampling, total sampling is a sample determination technique when all members of the population are used as samples. Data analysis in this study is a quantitative analysis using the Statistical Program of Partial Science (SPSS) software method which is used for the data calculation process. The results of the study show that: Organizational Culture does not affect teacher performance. Work motivation does not affect teacher performance. Work discipline does not affect teacher performance. Organizational Culture, Work Motivation and Work Discipline do not affect teacher performance.